Detrianonizacija madžarskega jezika - Kolláth, Anna (Jezik in slovstvo, 2006)
On the one hand, Hungarian is a vital European language and the national language of Hungary, while on the other hand, one fifth of its speakers live in a minority situation. The process of what is referred to as detrianonisation (detrianonizáció) of the Hungarian lnaguage, which is composed of various linguistic projects, has as its objective to rise the prestige of Hungarian as a minority language, while at he same time also being a model with its suppositions and solutions for other European languges in a similar situation.
Keywords: detrianonizacija; evropski jeziki; Hungarian; linguistics; lingvistika; madžarščina; manjšinski jeziki; projekti